Pengaruh Inflasi, Suku Bunga dan Nilai Tukar terhadap Return Saham Sektor Restoran Hotel dan Pariwisata - Vidyarini Dwita; Rose Rahmidani (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2012)
The purpose of this research is to examine the factor which is influence the stock return of sector in restaurant, hotels and tourism. The research used independent variables are inflation rate, interest rate and exchange rate. The population is firms in subsector of restaurants, hotels and tourism. Purposive sampling technique is used to taking sampel which only 8 firm’s as sampels. Time series data from stocks return in year 2005 – 2010. Multiple regresion for data analysis. Results shows that : 1). Inflation rate has significant negative influence on stock return ; 2) interest rate has unsignificant positively influence on stock return and 3) exchange rate has unsignificant positively infleunce on stock return.